Application of a load-bearing passive and active vibration isolation system in hydraulic drives. (September 2016) - Unruh, Oliver; Haase, Thomas; Pohl, Martin
Abstract: Hydraulic drives are widely used in many engineering applications due to their high power to weight ratio. The high power output of the hydraulic drives produces high static and dynamic reaction forces and moments which must be carried by the mounts and the surrounding structure. A drawback of hydraulic drives based on rotating pistons consists in multi-tonal disturbances which propagate through the mounts and the load bearing structure and produce structure borne sound at the surrounding structures and cavities. One possible approach to overcome this drawback is to use an optimised mounting, which combines vibration isolation in the main disturbance direction with the capability to carry the reaction forces and moments. This paper presents an experimental study, which addresses the vibration isolation performance of an optimised mounting. A dummy hydraulic drive is attached to a generic surrounding structure with optimised mounting and excited by multiple shakers. In order to improve the performance of the passive vibration isolation system, piezoelectric transducers are applied on the mounting and integrated into a feed-forward control loop. It is shown that the optimised mounting of the hydraulic drive decreases the vibration transmission to the surrounding structure by 8 dB. The presented study also reveals that the use of the active control system leads to a further decrease of vibration transmission of up to 14 dB and also allows an improvement of the vibration isolation in an additional degree of freedom and higher harmonic frequencies.